Improving health and housing outcomes through a simulation and economic model: an evidence-based protocol of a group model building approach to develop an agent-based model - Danielle M. Kline; Pranav Padmanabhan; Pranav Padmanabhan; Sarah E. Brewer; Sarah E. Brewer; Magdalena Cerdá; Elysia Versen; Katherine M. Keyes; Margot Kushel; Margot Kushel; Margot Kushel; Erin C. Wilson; et al. (Frontiers in Public Health, 2025)
IntroductionHomelessness in the United States increased every year since 2016, with a 38% increase from 2023 to 2024. Much of the increase is attributable to rising home and rent costs, economic hardship caused by the recent pandemic, and the ending of protective legislation. Notably, people who experience homelessness have an increased risk of substance use disorders, HIV infection and poorer HIV outcomes than people who are stably housed. The iHouse model aims to develop feasible, effective, and cost-effective tailored approaches to improve health outcomes in this population including life expectancy, overdose, and HIV.Methods and analysisThe study will employ Group Model Building methods and use insights from that process to develop an agent-based model simulating the dynamic processes contributing to HIV incidence and treatment, overdose, and life expectancy among people along the housing and homelessness continuum in Denver, CO and San Francisco, CA. The model will evaluate multiple outcomes from 4 conceptual dimensions: (1) movement along the housing continuum, (2) population health (overdose and HIV incidence and life expectancy), (3) budgetary impact, (4) economic value.Ethics and disseminationThis study has been approved by the Colorado Institutional Review Board at the University of Colorado under protocol 24–0878. The data generated by this protocol, the methodologies used, and the findings will be made available in a timely manner to other researchers. iHOUSE code and parameter values will be published in Git Hub, such that all model analyses can be reproduced by independent investigators. Documentation of all parameter estimates and model results will be published for independent review and confirmation. In addition, supplemental materials and appendices for the model will be shared on a publicly available website.